General Synod of the Church of Ireland. (13th December 2013) - Davey, Michael
<x content-type="archive" xml:space="preserve">Abstract</x> This year's programme looked, at first sight, to be a little daunting: 10 Bills and 26 motions to be dealt with in less than three days. However, on closer inspection the situation was not as bad as it seemed. Most of the Bills were of a technical or administrative nature: provision for the Cathedrals and Dignities of the Diocese of Tuam, Killala and Achonry, some tidying up of the Constitution and internal administration, and the abolition of the existing practice whereby members of General Synod are automatically proposed for re-election – an attempt, no doubt, to encourage greater turnover and variety among Synod members. It will be interesting to see how successful this will be.